2015
DOI: 10.2110/jsr.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Siliciclastic-Evaporite Strata In Subsurface and Outcrop: An Example From the Permian Nippewalla Group of Kansas, U.S.A

Abstract: Geologists tend to expect that rocks as they appear in outcrop are a very good approximation of the same strata in the subsurface. But this is not the case in mixed siliciclastic-evaporite units, strata that contain both a siliciclastic and an evaporite mineral component. Distinct differences in lithologic and stratigraphic descriptions of ancient siliciclastic-evaporite strata exist between outcrop and core. These differences present challenges in stratigraphic nomenclature, lithologic correlation, age determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It is important to note that the Leonardian–Guadalupian rocks of Kansas, the Sumner, Nippewalla and Quartermaster Groups, pose some challenges in their study. Because they contain evaporites, including halite, thicknesses and sedimentological descriptions are best represented in the subsurface; in outcrops, halite has been dissolved and only casts, moulds and pseudomorphs attest to depositional halite (Benison et al ., ). However, high recovery cores of evaporites are rare.…”
Section: Stratigraphic Contextmentioning
confidence: 97%
“…It is important to note that the Leonardian–Guadalupian rocks of Kansas, the Sumner, Nippewalla and Quartermaster Groups, pose some challenges in their study. Because they contain evaporites, including halite, thicknesses and sedimentological descriptions are best represented in the subsurface; in outcrops, halite has been dissolved and only casts, moulds and pseudomorphs attest to depositional halite (Benison et al ., ). However, high recovery cores of evaporites are rare.…”
Section: Stratigraphic Contextmentioning
confidence: 97%
“…In contrast, outcrops and shallow cores of these rocks are likely to be highly altered by halite dissolution by late-stage meteoric groundwaters (Gallois 2001). For example, a study of the Permian Nippewalla Group in outcrops and cores in Kansas showed that displacive halite (early diagenetic halite hosted by red mudstone) was the most common lithology in the subsurface, but its outcrop counterpart consisted of poorly cemented red mudstone (Benison et al 2015). The Carnduff-2 core represents the high preservation potential of the moderate subsurface depth.…”
Section: Can We Correlate the Mercia Mudstone Group In The Larne Basimentioning
confidence: 99%
“…A list of questions associated with the major and supplementary science topics appears in a data supplement table; overviews appear below. Coring is essential to (1) access buried upland records, (2) achieve continuous records in basinal regions, and (3) recover a pristine section suitable for application of various sedimentologic, geochemical, fluid-inclusion, rock-magnetic, magnetostratigraphic, paleontologic, and geochronologic approaches (i.e., Soreghan et al, 2015b;Benison et al, 2015). Additionally, during the course of both workshops, participants suggested considering expansion to a staged project that could incorporate coring in (1) multiple basins of western Europe and (2) in midpaleolatitude sites (e.g., China).…”
Section: Compelling Science Enabled By Coring the Permianmentioning
confidence: 99%
“…Intact and complete continental stratal records from the mid-Permian through Triassic of Pangaea are rare (in both outcrop and standard cores). Within the Anadarko Basin, outcrops are stratigraphically and lithologically incomplete due to intercalated halite in parts of the section, which dissolves at and near the surface (Benison et al, 2015). Furthermore, the gentle dip across a region with minimal relief creates limited outcrop opportunities.…”
Section: The Need For Coringmentioning
confidence: 99%